Industry Competitiveness Analysis Using Porter’s Five Forces: Indonesian Multi-industry Study Case - Siti Paramadita; Desman Hidayat (Forum Kerjasama Pendidikan Tinggi, 2022)
The COVID-19 pandemic and high competition have impacted the Indonesian economy. To survive the situation, companies need to understand their industry competitiveness. This study aims to analyze the industry factors in three different kinds of industries, namely aviation, education, and e-commerce industry. The method used in this study is a case study by explaining the industry’s background and characteristics and analyzing the industry factor by using Porter's Five Forces analysis in declining, stagnant, and improving business in the COVID-19 pandemic. Aviation, education, and e-commerce industry each represents the declining, stagnant, and improving industry in the COVID-19 pandemic situation. The result shows the different characteristics between each of the industry and how the industry forces, such as the threats of new entrants, the bargaining power of suppliers, the threat of substitutes, the bargaining power of buyers, and the rivalry among existing competitors can have different impacts on the industry competitiveness. This study gives insights on how an entrepreneur should face the competition in their industry. This study is limited to the research that is done in the pandemic situation, the number of industries researched, and the scope of the industry.